Household HIV Testing Uptake among Contacts of TB Patients in South Africa. - Kavindhran Velen; James J Lewis; Salome Charalambous; Liesl Page-Shipp; Flora Popane; Gavin J Churchyard; Christopher J Hoffmann (PLoS ONE)
Background In high HIV prevalence settings, offering HIV testing may be a reasonable part of contact tracing of index tuberculosis (TB) patients. We evaluated the uptake of HIV counselling and testing (HCT) among household contacts of index TB patients and the proportion of newly diagnosed HIV-infected persons linked into care as part of a household TB contact tracing study. Methods We recruited index TB patients at public health clinics in two South African provinces to obtain consent for household contact tracing. During scheduled household visits we offered TB symptom screening to all household members and HCT to individuals ≥14years of age. Factors associated with HCT uptake were investigated using a random effects logistic regression model. Results & discussion Out of 1,887 listed household members ≥14 years old, 984 (52%) were available during a household visit and offered HCT of which 108 (11%) self-reported being HIV infected and did not undergo HCT. Of the remaining 876, a total of 304 agreed to HCT (35%); 26 (8.6%) were newly diagnosed as HIV positive. In multivariable analysis, factors associated with uptake of HCT were prior testing (odds ratio 1.6; 95% confidence interval [CI]: 1.1-2.3) and another member in the household testing (odds ratio 2.4; 95% CI: 1.7-3.4). Within 3 months of testing HIV-positive, 35% reported initiating HIV care. Conclusion HCT as a component of household TB contact tracing reached individuals without prior HIV testing, however uptake of HIV testing was poor. Strategies to improve HIV testing in household contacts should be evaluated.